2012
DOI: 10.2112/jcoastres-d-11-00140.1
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Analyzing Land Use/Land Cover Changes in a Developing Coastal Town: A Case Study of Kusadasi, Turkey

Abstract: Modern man is an urban dweller. While early cities were small and produced little longstanding impact on their immediate environments, modern cities are vast and in some cases create over a hundred kilometers of uninterrupted urban areas. Cities are dependent on surrounding lands for food and other resources. As urban areas have grown, the populations of the countryside are diminishing at rapid rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Alphan, Yilmaz (2005) reported that agriculture has increasingly grown over marginal areas and urban development occurred at the expense of prime croplands in the eastern Mediterranean coast of Turkey. Other parts of the Turkish Mediterranean coast such as Kusadasi and Edremit bay faced similar problems resulting from development (Kara et al 2013;Irtem et al 2005). Intense human uses also cause complex LU/LC changes around the Mediterranean basin (Salvati, Sabbi 2011).…”
Section: Quantifying From-to Changesmentioning
confidence: 99%
“…Alphan, Yilmaz (2005) reported that agriculture has increasingly grown over marginal areas and urban development occurred at the expense of prime croplands in the eastern Mediterranean coast of Turkey. Other parts of the Turkish Mediterranean coast such as Kusadasi and Edremit bay faced similar problems resulting from development (Kara et al 2013;Irtem et al 2005). Intense human uses also cause complex LU/LC changes around the Mediterranean basin (Salvati, Sabbi 2011).…”
Section: Quantifying From-to Changesmentioning
confidence: 99%
“…Raw data sources typically include aerial photography and multispectral and hyperspectral optical sources, such as those described thus far. Methods for classifying urban land covers include manual classifiers [19], fuzzy and hard classifiers [20], expert systems [14,21], object-based methods [22], machine learning [23], subpixel [24], and urban spectrometry [25].…”
Section: Urban Compositionmentioning
confidence: 99%
“…For instance, using GIS to assess landscape dynamics also starting from digital sources (e.g. photo archives) (Popa, & Enache, 2016), using geo-tagged photos collected from Flickr and proposing a geo-clustering algorithm (Spyrou et al, 2017), using photographs depicting the urban landscape as a method for social critique (Kim, 2016), using satellite images to monitor and analyse landscape changes (land use and land cover) in coastal areas (Kara et al, 2013, El Banna et al, 2009). In the field of Cultural and Political Geography, research explored the use of propaganda photographs and the promotion of geographical education, while producing nationalist landscapes during the process of nation-building (Tyner et al, 2015), and also explored the use of photos in enabling cultural interaction and understanding (Lemmons et al, 2014).…”
Section: Introductionmentioning
confidence: 99%